Zohir dan Muawwal dalam Ushul Fiqh: Analisis Konsep, Contoh Penerapan, dan Batasan Ta’wil dalam Penetapan Hukum Islam - Risma Oktaviana; M. Timbul Cahyadi; Arif Zandi (CV. ITTC INDONESIA, 2025)
This study examines the concepts of Zahir and Muawwal in the science of Ushul Fiqh, which play an important role in understanding the meanings of Qur’anic and Hadith texts (nusus). Zahir refers to a wording whose meaning is clear and can be understood directly according to its apparent indication in the Arabic language, whereas Muawwal refers to a wording whose apparent meaning is interpreted away from its literal sense due to the presence of evidence that necessitates such interpretation.This research employs a descriptive method with a library research approach by examining classical and contemporary literature in the field of Ushul Fiqh. The findings indicate that the fundamental rule in interpreting nusus syar‘iyyah is to adhere to their zahir meaning unless there is evidence that redirects them to another meaning. Ta’wil is only acceptable when certain conditions are met, such as the presence of strong supporting evidence and conformity to linguistic principles.Thus, understanding Zahir and Muawwal becomes essential in interpreting the texts of the Shari‘ah proportionally and in preventing the Muslim community from falling into errors in comprehending Islamic law.